Protective Effect of Maternal First-Trimester Low Body Mass Index Against Macrosomia: A 10-Year Cross-Sectional Study - Sun, Yongqing; Zhang, Man; Liu, Ruixia; Wang, Jingjing; Yang, Kai; Wu, Qingqing; Yue, Wentao; Yin, Chenghong (Frontiers in Endocrinology, 2022)
Objective: To elucidate the relationship between maternal first-trimester low body mass index (BMI) and macrosomia, stratifying by maternal age, parity, gestational diabetes mellitus (GDM) status, fetal sex, and season of delivery. Methods: This was a retrospective cohort study from January 1, 2011 to June 30, 2021, 84900 participants were included. The predictive performance of maternal first-trimester and parental pre-pregnancy BMI for macrosomia were assessed using the area under the receiver-operating-characteristics curve (AUC). Multivariate Logistic regression analyses were performed to evaluate the independent effect of maternal first-trimester low BMI on macrosomia. Interactions were investigated to evaluate the potential variation of the effect of first-trimester low BMI across different groups. Furthermore, interactions were also examined across groups determined by multiple factors jointly: (a) parity, maternal age, and GDM status; (b) GDM status, fetal sex, and season of delivery. Results: The proportion of macrosomia was 6.14% (5215 of 84900). Maternal first-trimester BMI showed significantly higher AUC (all Delong tests: P < 0.001). The protective effect of maternal first-trimester low BMI on macrosomia remained significant after adjusting for all confounders of this study (adjusted odds ratios (aOR) = 0.37, 95% CI: 0.32-0.43). Maternal first-trimester low BMI was inversely associated with macrosomia, irrespective of maternal age, parity, GDM status, season of delivery, and fetal sex. The protective effect was most pronounced among pregnant women without GDM aged 25-to-29-year-old, irrespective of parity (multipara: aOR = 0.32, 95% CI: 0.22-0.47; nullipara: aOR = 0.32, 95% CI: 0.24-0.43). In multipara with GDM, protective effect of low BMI was only observed in the 30-to-34-year-old group (aOR = 0.12, 95% CI: 0.02-0.86). For pregnant women without GDM, the protective effect of maternal first-trimester low BMI against macrosomia was weakest in infants born in winter, irrespective of fetal sex (female: aOR = 0.45, 95% CI: 0.29-0.69; male: aOR = 0.39, 95% CI: 0.28-0.55). Conclusion: Maternal first-trimester low BMI was inversely associated with macrosomia, and the protective effect was most pronounced among 25-to-29-year-old pregnant women without GDM and was only found among 30-to-34-year-old multipara with GDM. Fetuses born in winter were least benefited from maternal first-trimester low BMI among mothers without GDM.